Is Socrates a Prophet? (In Light of the Views of His Contemporaries and the Main Commentators) - Ghaffari, Hossein (Sophia, 2011)
Everybody acknowledges the importance of Socrates’ role and influence on the history of philosophy, as well as on the culture of humanity. He is also considered to be the first martyr of virtue and wisdom in human history. In spite of this, even though most Western commentators recognize the elevated meanings and high level of Socratic wisdom, they refuse to consider it to have a supra-human source and to be divine prophecy. In this article and through the analysis of Socrates’ words and speeches, which can be found in authentic sources such as some of Plato’s writings, the author aims to prove the truth of Socrates’ claim according to which he had the gift of prophecy. By putting together rational proofs and historical clues from his life, we will underline the veracity of such a claim. A part of the article will be dedicated to underlining the fact that our reasoning is based on authentic and historical references of Socrates’ speeches, which are mainly mentioned in Plato’s Apology. By quoting the main and most important commentators’ views in this field, we will therefore endeavor to show that there is a sort of general consensus among most commentators to consider this treatise to be an historical document. The importance as well as main outcome of this article is that if we accept this theory, the general outlook of the history of philosophy will change radically. In addition, the claim that wisdom has a divine source, which is mentioned repeatedly in the content of divine wise men’s words and in some Islamic traditions, will be confirmed. Moreover, the link between spiritual truths and human reasoning will be corroborated and underlined.